Non-Penal Efforts in Overcoming Crime of Corruption by Building an Anti-corruption Culture for "Didikan Subuh" Participants in Padang - Pratimaratri, Uning; Firman, Boby; Musta, Arif Paria (Activa Yuris: Jurnal Hukum, 2023)
This study examines the concept of integration of Anti-Corruption Education at "Subuh" Education Program in Padang City. Corruption is an extraordinary crime or extraordinary crime, so it needs extraordinary handling as well. Viewed from the organic theory, the handling of criminal acts of corruption is equipped with a complete structure. Judging from the substance of the law, it has been widely supported by complete laws and regulations. From the aspect of legal culture, several policies have been issued that integrate Anti-Corruption Education into the learning curriculum in schools. However, these efforts have not yielded significant results. The rate of corruption is still said to be high. In Padang City, an average of 39 cases are submitted to the Corruption Court, Padang District Court. The approach that needs to be taken is a religious approach. The Islamic religious approach is carried out by integrating Anti-Corruption Education in the "Subuh" Education Program. "Didikan Subuh" is an Islamic Education Program that was born and developed inÂ Minangkabau.Â Subuh Education is a functional and practical conception of Islamic Education at dawn with activities centered in the Mosque and Mushalla. Researchers used the Legal System Theory from Laurence M. Friedman and the Functional Structure Theory from Talcott Parsons. This research is normative legal research. The data source consists of secondary data. Data were analyzed qualitatively.